Evaluation of visual acuity and macular thickness post focal laser with and without supplementary honey in diabetic macular oedema - Rahim, Raihan Abd (2016)
Introduction Diabetic macular oedema (DMO) is a significant cause of vison loss in the diabetic patients. Laser is the standard treatment for DMO. Chronic inflammatory also has an important role in the pathogenesis of DMO. Tualang honey with anti-inflammatory and anti-oxidant properties has a potential as an adjunct treatment for DMO. Objective To compare LogMAR best corrected visual acuity (BCVA) and central macular thickness (CMT) at 3 months post laser treatment between those with and without honey supplement in DMO. Methods A prospective randomized controlled study was conducted in Hospital Universiti Sains Malaysia between April 2013 and August 2015. Patient with clinically significant macular oedema (CSMO) was selected and was randomized by using randomised envelope technique into 2 groups; laser without honey group and laser with honey group. Patients were evaluated for LogMAR BCVA and CMT pre treatment and at 3 months post treatment. LogMAR BCVA was assessed using LogMAR chart and CMTwas measured using Heidelberg Spectralis OCT. Results A total of 52 patients were recruited (laser group without honey: 26 patients and laser with honey group: 26 patients) into this study. There was a significant improvement of mean LogMAR BCVA at 3 months post treatment in DMO patients treated with laser alone (p=0.002). However, there was no significant difference of the mean LogMAR BCVA in DMO patients treated with laser between those with and without honey supplement at 3 months post treatment (p=0.448). There was also no significant difference of mean CMT (p=0.881) at 3 months post laser treatment between those with and without honey supplement. There was no side effect of honey noted in patients consumed tualang honey. Conclusion Tualang honey used as adjunct with standard focal/grid laser has no additional improvement in both visual acuity and CMT compared to laser alone.